2011
DOI: 10.1186/1757-7241-19-27
|View full text |Cite
|
Sign up to set email alerts
|

High mobility group box protein-1 (HMGB-1) as a new diagnostic marker in patients with acute appendicitis

Abstract: BackgroundThe aim of this prospective study was therefore to evaluate the diagnostic value of preoperative serum High Mobility Group Box Protein-1 (HMGB-1) levels in patients with Acute Appendicitis (AA) who show normal white blood cell count (WBC) counts.MethodOur study was carried out from October 2010 through November 2010 and included 20 healthy control group participants and 60 patients who presented at the emergency department of Erzurum Training and Research Hospital in Turkey with acute abdominal pain … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
20
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(22 citation statements)
references
References 28 publications
1
20
1
Order By: Relevance
“…HMGB1 is involved in pathophysiological pain from cancer (Tong et al, 2010), acute appendicitis (Albayrak et al, 2011), type 2 diabetes (Ren et al, 2012), bladder pain (Tanaka et al, 2014), and neuropathic pain (Maeda et al, 2013). Neuropathic pain is caused by nervous system injury and persistent alterations in pain sensitivity.…”
Section: Hmgb1 and Diseasementioning
confidence: 99%
See 1 more Smart Citation
“…HMGB1 is involved in pathophysiological pain from cancer (Tong et al, 2010), acute appendicitis (Albayrak et al, 2011), type 2 diabetes (Ren et al, 2012), bladder pain (Tanaka et al, 2014), and neuropathic pain (Maeda et al, 2013). Neuropathic pain is caused by nervous system injury and persistent alterations in pain sensitivity.…”
Section: Hmgb1 and Diseasementioning
confidence: 99%
“…In the gastrointestinal tract, increased levels of HMGB1 have positively correlated with intestinal barrier dysfunction and colonic inflammation in mice (Dave et al, 2009; Liu et al, 2006; Luan et al, 2010; Maeda et al, 2007; Sappington et al, 2002; Wu et al, 2009; Yang et al, 2009a). Moreover, fecal HMGB1 is a novel biomarker of intestinal mucosal inflammation in patients with inflammatory bowel disease (Vitali et al, 2011), whereas serum HMGB1 is diagnostic marker in patients with acute appendicitis (Albayrak et al, 2011; Soreide, 2011; Wu et al, 2012a). TLR4 and TLR2 are required for the HMGB1-mediated inflammatory response and injury in inflammatory bowel disease, as well as necrotizing enterocolitis (Dai et al, 2010; Downard et al, 2011; Lu et al, 2013b; McDonnell et al, 2011; Zamora et al, 2005).…”
Section: Hmgb1 and Diseasementioning
confidence: 99%
“…Recent clinical studies have shown that HMGB1 is a potential diagnostic or prognostic biomarker in a variety of inflammatory disorders [1012] and cancers [13–19]. One group from the USA provided the first evidence that HMGB1 was highly expressed in both tissues and sera of mesothelioma patients [20].…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, some biomarkers most frequently investigated in this context are cytokines, adhesion molecules, interleukins-especially interleukin-6, procalcitonin (PCT), urinary leucine-rich alpha-2-glycoprotein (LRG), S100A8/A9, high mobility group box-1 protein (HMGB1), and D-lactate [514]. …”
Section: Laboratory Adjuncts In the Diagnosis Of Acute Appendicitismentioning
confidence: 99%